Oncological Treatment Considerations Differ across Surgical Subspecialties Treating Malignant Peripheral Nerve Sheath Tumors: An International Survey. (28th February 2020) - Martin, Enrico; Slooff, Willem-Bart M.; van Houdt, Winan J.; van Dalen, Thijs; Verhoef, Cornelis; Coert, J. Henk
Abstract : Background . Malignant peripheral nerve sheath tumors (MPNSTs) are rare and aggressive soft tissue sarcomas (STS) that, because of their origin, are operated by several surgical subspecialties. This may cause differences in oncologic treatment recommendations based on presentation. This study investigated these differences both within and between subspecialties. Methods . A survey was distributed among several (inter)national surgical societies. Differences within and between subspecialties were analyzed by χ 2 -tests. Results . In total, 30 surgical oncologists, 30 neurosurgeons, 85 plastic surgeons, and 29 "others" filled out the survey. Annual caseload, tumor sites operated, and fellowship training differed significantly between subspecialties. While most surgeons agreed upon preoperative use of MRI, the use of radiological staging and FDG-PET use differed between subspecialties. Surgical oncologists agreed upon core needle biopsies as an ideal type of biopsy while other subspecialties differed in opinion. On average, 53% of surgeons always consider preservation of function preoperatively, but 42% would never perform less extensive resections for function preservation. Respondents agreed that radiotherapy should be considered in tumor sizes >10 cm, microscopic, and macroscopic positive margins. A preferred sequence of radiotherapy administration differed between subspecialties. There was no consensus on indications and sequence of administration of chemotherapy in localized disease. Conclusion . Surgical oncologists generally agree on preoperative diagnostics; other subspecialties do not. Considering the preservation of function differed among all subspecialties. Surgeons do agree on some indications for radiotherapy, yet the use of chemotherapy in localized MPNSTs lacks consensus. A preferred sequence of multimodal therapy differs between and within surgical subspecialties, but surgical oncologists prefer neoadjuvant radiotherapy.